A CASE OF TOXIC CYSTIC LEUKOENCEPHALOPATHY AFTER ANTI-PSYCHOTIC OVERDOSE. (29th November 2012) - Cameron Smail, R; Tetlow, H; Mazzar Siddiqi, S; Stevens, S; McColgan, P
Abstract : We present the case of a 41-year-old lady who was admitted following an overdose of olanzapine, venlafaxine, quetiapine and propranolol. She was intubated in ITU and treated for aspiration pneumonia, ARDS, neuroleptic malignant syndrome, rhabdomyolysis and seizures. CT head on day 8 of admission was normal. A further CT scan on day 18 for slow weaning indicated low attenuation within the periventricular deep white matter suggestive of watershed infarcts. Over the next weeks she was slow to improve, with a flaccid paralysis with no pain response or reflexes. On Day 40, and MRI brain showed bilateral symmetrical signal abnormality within the deep white matter within the frontal, parietal and temporal lobes with central cystic cavitation. Over the next weeks, she remained flaccidly tetraparetic, but could respond appropriately to questions with blinking and eye movements. Discussion: The evidence of white matter tract destruction shown on MRI is unusual in this clinical context. We cannot find other reports of toxic effects of antipsychotics or neuroleptic malignant syndrome causing such prominent loss. It is not a typical distribution for watershed infarcts. Given the distribution, a severe form of PRES was another differential. Conclusion: We demonstrate that cystic leukoencephalopathy can occur following anti-psychotic medication overdose. This may result either directly from toxic drug effects, or indirectly after neuroleptic malignant syndrome. Clinicians are advised to be aware of this rare complication.